Synthesized of Double Layer Thin Film ZnO/ZnO:Ag by Sol-Gel Method for Direct Blue 71 Photodegradation - Heri Sutanto; Singgih Wibowo; Eko Hidayanto; Iis Nurhasanah; Hady Hadiyanto (Dept. of Chemical Engineering, Diponegoro University, 2015)
The objective of this paper is to synthesize and to characterize a single and a double layer ZnO and ZnO/ZnO:Ag thin films and their application for degradation of direct blue 71. Double layer (DL) thin films of zinc oxide and silver-doped zinc oxide (ZnO/ZnO:Ag) were deposited on the substrate glass by using sol-gel spray coating technique. Ag doping variations (2, 4, 6 and 8 %mol) into ZnO were studied. X-Ray Diffractometer (XRD) and UV-Vis spectrophotometer were used to analyze structure and optical properties of thin films. Direct Blue 71 (DB71) was used for photocatalytic evaluation under UV light irradiation. XRD result showed that all prepared thin films have wurtzite structure with better crytalinity compared to double layer preparation and increasing concentration of Ag doping. UV-Vis transmittance spectra showed that decreasing of transparency of films followed by DL preparation and Ag doping concentration. By using envelope method, energy gap of films can be determined. ZnO/ZnO:Ag 6% (DL 6%) indicated the smallest energy gap 3,038 eV. The highest DB71 degradation result under UV light irradiation was reached by DL 6% with 55.43% and 8.56 x 10-3 min-1 for photocatalytic efficiency and photodegradation rate, respectively.